Ultimate Happiness Prescription : 7 Keys to Joy and Enlightenment - Deepak Chopra (Rider, 2010)
Chopra shows how to experience joy in spite of living in difficult or trying times. By looking through the lens of our contemporary understanding of consciousness, combined with Eastern philosophy, he has created a set of principles for living with ease. The result is an inspiring and instructive journey that leads to a prescription for living life mindfully, with a light heart and with effortless spontaneity - a prescription only Dr Deepak Chopra could write. With words like 'depression' and 'recession' in the air, he underlines the importance of keeping an eye on the positive aspects of life and finding ways to experience joy no matter what is happening to you.